Anti-Soviet Resistance in Klaipėda Territory in 1945–1953 - Pušinskytė, Lijana (Genocidas ir rezistencija, 2009)
The paper gives an analysis of the problem of anti- Soviet resistance in the Klaipėda Territory and the city of Klaipėda which lacked separate attention of historiography so far. The purpose is to discuss anti-Soviet resistance in the Klaipėda Territory and the city of Klaipėda in 1945–1953. Conditions that predetermined the formation of anti- Soviet resistance in the Klaipėda Territory and the city of Klaipėda as well as the specificity of partisan resistance in the Klaipėda Territory are underlined. During World War II, the city of Klaipėda suffered enormous losses and was left almost without the inhabitants. After the war, conditions for the emergence of anti-Soviet resistance in the Klaipėda Territory were not favourable. Since people with different national, ideological and religious views moved here, their relations were quite complicated. This predetermined the fact that in the Klaipėda Territory in 1945 a large, active and united resistance movement against the Soviet regime did not rise. A conflict between the population and Soviet authorities (i.e. a partisan war) in Greater Lithuania was transferred in the essence to the plane of the relations between the new settlers and repatriants. This makes it possible to speak about the possible specific conditions of anti-Soviet resistance in the Klaipėda Territory in the context of the territory of Lithuania and about the specificity of anti-Soviet resistance itself. Research revealed that in the Klaipėda Territory in 1948–1953 two partisan squads – “Geležinis vilkas“ and “Rambynas” (“Pilis”) were active. They fought in the Darius district of Butageidis brigade of Kęstutis command (Klaipėda and Šilutė counties). Archival sources show that pre-war Klaipėda Territory residents and persons of German nationality joined the partisan squads that operated in the Klaipėda Territory outskirts.